Evaluation of dominant factors for stability of grid‐connected inverters based on impedance sensitivity analysis - Lei Fang; Longji Feng; Chengbo Chu; Jun Xu; Rong Wu; Qingchuan Fan (IET Renewable Power Generation)
Abstract This article proposes a method for evaluating the dominant factors of grid‐connected inverters based on impedance models, which can achieve quantitative calculation of the dominant factors of system stability. First, an impedance model was established, and an analysis method based on the impedance model was proposed to calculate the absolute sensitivity. The control and circuit parameters of the grid‐connected inverter were calculated, and the impact trend of each parameter on system stability was obtained. Then, in order to eliminate the influence of dimensions between various parameters and achieve traceability of the dominant factors of stability, an absolute sensitivity stability analysis method was proposed to analyze the influencing factors of different frequency bands, and based on this, a suppression scheme of harmonic resonance is proposed. Finally, the accuracy of the method was verified through impedance sweep based on grid‐connected inverters.